1

I am currently trying to add an equation to my thesis and due to the length of it I would like to use short hand to split the equation up. What I would like to achieve is a equation with two line breaks, followed by a left aligned where, and the other equations under one gathered environment with the equation number aligned to the top line. I have achieved most of this but I cannot get the "where" line left aligned in a gathered environment, I have tried \intertext and it doesn't appear to work when using gathered. Any suggestions?

\begin{equation}\label{eq:triclinic(hkl)}
        \begin{gathered}[t]
        \frac{1}{d^2} = \frac{1}{V^2} (S_{11}h^2 + S_{22} k^2 + S_{33} \ell^2 + 2S_{12}hk + 2S_{23}k\ell + 2S_{13}h\ell)\\~\\
        \text{where}\\~\\
        V      = abc \sqrt{1 - cos^2(\alpha) - cos^2(\beta) - cost^2(\gamma) + 2cos(\alpha) cos(\beta) cos(\gamma)}\\
        S_{11} = b^2c^2sin^2(\alpha)\\
        S_{22} = a^2c^2sin^2(\beta)\\
        S_{33} = a^2 b^2 sin^2 (\gamma)\\
        S_{12} = abc^2 (cos(\alpha) cos(\beta) - cos(\gamma))\\
        S_{23} = a^2bc (cos(\beta) cos(\gamma) - cos(\alpha)\\
        S_{13} = ab^2c (cos(\gamma) cos(\alpha) - cos(\beta)\\
        \end{gathered}
    \end{equation}
  • Welcome to TeX.SX! Please make your code compilable (if possible), or at least complete it with \documentclass{...}, the required \usepackage's, \begin{document}, and \end{document}. That may seem tedious to you, but think of the extra work it represents for TeX.SX users willing to give you a hand. Help them help you: remove that one hurdle between you and a solution to your problem. – dexteritas Aug 30 '18 at 16:06
  • welcome to tex.se! your question is not "overleaf" specific, so i delete its tag. try to use gather only. – Zarko Aug 30 '18 at 16:06
1

You can set this in an align and use \notag to remove any equation numbers for equations you don't need numbered:

enter image description here

\documentclass{article}

\usepackage{mathtools}

\begin{document}

Original equation
\begin{equation}
  \begin{gathered}[t]
    \frac{1}{d^2} = \frac{1}{V^2} (S_{11}h^2 + S_{22} k^2 + S_{33} \ell^2 + 2S_{12}hk + 2S_{23}k\ell + 2S_{13}h\ell)\\~\\
    \text{where}\\~\\
    V      = abc \sqrt{1 - cos^2(\alpha) - cos^2(\beta) - cost^2(\gamma) + 2cos(\alpha) cos(\beta) cos(\gamma)}\\
    S_{11} = b^2c^2sin^2(\alpha)\\
    S_{22} = a^2c^2sin^2(\beta)\\
    S_{33} = a^2 b^2 sin^2 (\gamma)\\
    S_{12} = abc^2 (cos(\alpha) cos(\beta) - cos(\gamma))\\
    S_{23} = a^2bc (cos(\beta) cos(\gamma) - cos(\alpha)\\
    S_{13} = ab^2c (cos(\gamma) cos(\alpha) - cos(\beta)\\
  \end{gathered}
\end{equation}

Proposed improvement
\begin{align}
    \frac{1}{d^2} &= \frac{1}{V^2} \bigl( S_{11}h^2 + S_{22} k^2 + S_{33} \ell^2 + 2S_{12}hk + 2S_{23}k\ell + 2S_{13}h\ell \bigr) \\
\shortintertext{where}
         V &= a b c \sqrt{1 - \cos^2(\alpha) - \cos^2(\beta) - \cos^2(\gamma) + 2 \cos(\alpha) \cos(\beta) \cos(\gamma)} \notag \\
    S_{11} &= b^2 c^2 \sin^2(\alpha) \notag \\
    S_{22} &= a^2 c^2 \sin^2(\beta) \notag \\
    S_{33} &= a^2 b^2 \sin^2 (\gamma) \notag \\
    S_{12} &= a b c^2 \bigl( \cos(\alpha) \cos(\beta) - \cos(\gamma) \bigr) \notag \\
    S_{23} &= a^2 b c \bigl( \cos(\beta) \cos(\gamma) - \cos(\alpha) \bigr) \notag \\
    S_{13} &= a b^2 c \bigl( \cos(\gamma) \cos(\alpha) - \cos(\beta) \bigr) \notag
\end{align}

\end{document}
  • You missed some cos’s. ;-) I’d also remove all those parentheses since angles in trigonometric functions don’t need them. – Ruixi Zhang Aug 30 '18 at 16:40
  • @RuixiZhang: Thanks for identifying the missing \cos's. I've left the brackets in there because this might be personal preference. – Werner Aug 30 '18 at 16:52
1

I propose this layout:

\documentclass{article}

\usepackage{mathtools}

\begin{document}

\begin{align}
    \frac{1}{d^2} &= \frac{1}{V^2} \bigl( S_{11}h^2 + S_{22} k^2 + S_{33} \ell^2 + 2S_{12}hk + 2S_{23}k\ell + 2S_{13}h\ell \bigr) \\
\intertext{where \quad$ \begin{array}[t]{|l@{}}
         V = a b c \sqrt{1 - \cos^2\alpha - \cos^2\beta - \cos^2\gamma + 2 \cos\alpha \cos\beta \cos\gamma} \\[1ex] \begin{aligned}[t]
    S_{11} &= b^2 c^2 \sin^2\alpha \qquad &
    S_{12} &= a b c^2 \bigl( \cos\alpha \cos\beta - \cos\gamma \bigr) \\
    S_{22} &= a^2 c^2 \sin^2\beta & S_{23} &= a^2 b c \bigl( \cos\beta \cos\gamma - \cos\alpha \bigr)\\
    S_{33} &= a^2 b^2 \sin^2 \gamma & S_{13} &= a b^2 c \bigl( \cos\gamma \cos\alpha - \cos\beta \bigr)
\end{aligned}
\end{array}$} \notag
\end{align}

\end{document} 

enter image description here

0

There is no need to have everything in a single display:

\documentclass{article}
\usepackage{amsmath}

\begin{document}

\begin{equation}\label{eq:triclinic(hkl)}
\frac{1}{d^2} = \frac{1}{V^2} (
  S_{11}h^2 + S_{22} k^2 + S_{33} \ell^2 +
  2S_{12}hk + 2S_{23}k\ell + 2S_{13}h\ell
)
\end{equation}
where
\begin{align*}
V      &= abc \sqrt{
  1 - \cos^2(\alpha) - \cos^2(\beta) - \cos^2(\gamma) +
  2\cos(\alpha) \cos(\beta) \cos(\gamma)
}\\
S_{11} &= b^2c^2\sin^2(\alpha)\\
S_{22} &= a^2c^2\sin^2(\beta)\\
S_{33} &= a^2b^2\sin^2(\gamma)\\
S_{12} &= abc^2 (\cos(\alpha) \cos(\beta) - \cos(\gamma))\\
S_{23} &= a^2bc (\cos(\beta) \cos(\gamma) - \cos(\alpha)\\
S_{13} &= ab^2c (\cos(\gamma) \cos(\alpha) - \cos(\beta)
\end{align*}

\end{document}

enter image description here

You might use gather* in the bottom display (no trailing \\, beware), if you prefer.

Use \cos and \sin for the trig functions.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.